Moderasi Beragama pada Tradisi Nyadran dalam Membangun Hubungan Masyarakat Plural di Desa Bungah - Rofiqoh, Nur Indah; Afriyanti, Dwi (Proceedings of International Conference on Muslim Society and Thought, 2024)
The reality of conflict or friction between individual and group interests in various regions. It cannot be separated from being a vehicle for society, because there are good values that the community practises. In the present context, the issue of harmony among followers of a religion remains relevant. In the meantime, local traditions are less popular, and the study of the Nyadran tradition has not received a lot of attention. The tradition of nyadran is rooted in the Dukuh Muslim community, which follows and implements it. In developing social relations in a plural society in Dukuh village, Bungah district, this dissertation examines the moderation of religion in the nyadran tradition. The research aims to analyse and discover the nyadran traditions that are carried out within the community, activities, symbols and values of religious moderation in this tradition among peoples of Dukuh Village, Bungah Gresik District. Qualitative naturalistic field research methods are used. The analysis data shall be compiled, classified, processed and the next stage is interpretation and conclusion. Data mining by means of documentation, observation and interviews. In three main formulations of activities, symbols and values, the nyadran tradition has been identified in this research. The Nyadran tradition is a tradition that strengthens the moderation of religion in aspects of local wisdom. The solidarity of the Nyadran tradition is reflected in Nyadran as a ritual. Nyadran is an important element in maintaining religious moderation and part of cultural education for communities. The meaning of education taught by Islamic religious education. This research shows that for developing social relations in a plural society there is an important role to be played by moderate Islamic education based on the culture traditions of the country.